Linguistic Diversity at Risk: Description of Endangered Languages in Papua - Kafryawan, Wira; Mursyid, Andi Miftahul Maulidil (Fakultas Tarbiyah IAIN Fattahul Muluk Papua, 2024)
Language and linguistic diversity in Papua are on the edge of extinction. Merely few languages have been documented and hundreds of them are still hitherto underdescribed or undescribed. The paper provides a brief description regarding the situation and condition of endangered languages in Papua by using a descriptive qualitative. The data was outlined in the shortlisted information based on Fishman’s EGIDS involving dormant languages, nearly extinct languages, and moribund languages. As a result. 42 languages in Papua are generally categorized as critically endangered. Moreover, rapid vitality decline is driven by several issues such as cultural assimilation, economic pressures, breakdown of language transmission, and the dominance of superior languages. Describing and documenting those endangered languages is crucial for preserving their unique linguistic features, cultural heritage, and traditional knowledge. Without immediate and comprehensive documentation, the richness of linguistic diversity in Papua stands to be irretrievably gone.